LABOR MARKET UNDER THE CONDITIONS OF THE GLOBAL PANDEMIA - Agumbaeva Asiya Erlikovna; Gabdualieva Raushan Smadinovna; Tulegenova Ainagul Utegenovna; Kurmantayeva Bakhytgul Kurmantayevna; Tlessova Zhanat Amangosovna; Abuova Zhemis Uzakbaevna (Scientific Journal of Pedagogy and Economics, 2021)
The labor market in Kazakhstan, as it is changing around the world and is probably transforming beyond recognition in a year. A pandemic dictates its own rules to the labor market: many companies have begun to cut staff costs, parting even with valuable employees. In conditions of forced self-isolation during the coronavirus epidemic, for many people, the problem of employment came first. People working in quarantined sectors are left without means of subsistence and are forced to look for a place in other areas. The decline in quantitative indicators since the beginning of March is observed in almost all sectors. Previously, it was possible to work for decades by the same standards, but now approaches to work change several times a year. In conditions when many competencies quickly become obsolete, “flexible skills” come to the fore - logical and critical thinking, creativity, adaptability to changes, the ability to build relationships with people and solve complex problems. The pandemic will bring significant changes to the labor market. According to the authors, self-development and the acquisition of new skills will be the only trend in the modern labor market. In order to successfully overcome the crisis, it is necessary to provide affordable financing for business and the public. In the conditions of this kind of crisis, it is necessary to increase the responsibility and coordination of all state bodies and their orientation towards job creation and employment. To this end, it is proposed to strengthen the functions of state bodies in facilitating information support to business in times of crisis. It is also necessary to ensure the complete digitalization of public services and the provision of high-quality and relevant data on the labor market to the population.